STUDY OF CHRISTIAN ETHICAL VALUES ACCORDING TO 1 PETER 3: 14-17 AND ITS IMPLEMENTATION IN RELIGIOUS MODERATION IN INDONESIA - Hendarwoto, Yermia; Sutrisno, Sutrisno (Didache: Jurnal Teologi dan Pendidikan Kristen, 2023)
The biblical passage emphasizes virtues such as gentleness, respect, and endurance in the face of adversity, providing a foundational framework for ethical conduct. Through an exploration of the cultural and societal context in Indonesia, this abstract seeks to elucidate how these values can be implemented to promote interfaith dialogue, social responsibility, and a culture of understanding, thereby contributing to religious moderation and harmony. The research draws upon biblical exegesis, cultural studies, and contemporary examples to illuminate the relevance and impact of Christian ethical values in the Indonesian context, offering insights for both scholars and practitioners engaged in interfaith initiatives and the promotion of tolerance.This research was conducted by carrying out exegesis of 1 Peter 3: 14-17 which is believed to provide a way to be moderate and afterward conducting descriptive qualitative research by conducting interviews with witnesses and sources. In this study, it was found that the ability and strength of Christians in carrying out the practice of religious moderation is not based on ethical and moral awareness as human beings but is based on understanding and total self-surrender to sanctify Christ in the heart, so that a person can be patient in suffering, strong enough to forgive the guilty, stand firm in righteousness and godliness.